Survey of Low Income Aged and Disabled, 1973-1974 ([Verlag nicht ermittelbar], 1984)
This data collection contains the results of the Survey of Low Income Aged and Disabled (SLIAD), conducted in 1973-1974 in order to collect demographic and socioeconomic data necessary for assessing the effect of the Supplemental Security Income (SSI) program on potential recipients. After January 1, 1974, SSI replaced the state-administered welfare programs of Old Age Assistance (OAA), Aid to the Blind (AB), and Aid to the Permanently and Totally Disabled (APTD) and was meant to improve the economic well-being of the adult poor. A national sample of about 18,000 low-income aged, blind, and/or disabled adults was interviewed in 1973, and reinterviewed in 1974, after SSI was implemented. The 1974 re-interviews were conducted only with persons successfully interviewed in 1973. No new cases were added to replace first-year losses, nor were cases dropped because they no longer met SSI eligibility. Part 1 contains data gathered from a sample made up of aged and disabled persons who received OAA, AB, and/or APTD payments in 1973. Part 2 contains data gathered from a sample of low-income aged and disabled people in the general population (generated from Current Population Survey samples). The United States Census Bureau conducted the interviews and collected the data. The 1973 survey placed great emphasis on financial matters. Each respondent was asked to report income received in the preceding month and year by each of three general classes of persons in the household. The questionnaire listed more than 15 income sources including payments and awards from almost every transfer program possible, earnings from jobs and businesses, gifts, and dividends. The financial section of the questionnaire also included items aimed at establishing the value of owned property, savings and investments, the amount of indebtedness, and the amount spent for food, shelter, and other recurring household expenditures. For the most part, the remainder of the questionnaire concerned (1) household composition, (2) personal history, (3) health, health care, and the capacity for self-maintenance, (4) standard of living, as represented by housing, diet, travel, and recreation, (5) factors that might affect the relation between income and standard of living (e.g., personal preference, physical capacity, and access), and (6) attitudinal response to these conditions, circumstances, and types of status. The 1974 survey was similar in that it asked almost all of the earlier income and asset questions, but added a section on SSI payments. It also collected more detail on household living expenses. It did not repeat the biographical section or the inventory of health conditions from the 1973 survey, but did contain new questions on a spouses' funeral expenses as well as the respondent's experience with SSI.